Cross‐generational effects of temperature on flight performance, and associated life‐history traits in an insect. (28th August 2013) - Ferrer, A.; Dorn, S.; Mazzi, D.
Abstract: Nongenetic parental effects may affect offspring phenotype, and in species with multiple generations per year, these effects may cause life‐history traits to vary over the season. We investigated the effects of parental, offspring developmental and offspring adult temperatures on a suite of life‐history traits in the globally invasive agricultural pest Grapholita molesta . A low parental temperature resulted in female offspring that developed faster at low developmental temperature compared with females whose parents were reared at high temperature. Furthermore, females whose parents were reared at low temperature were heavier and more fecund and had better flight abilities than females whose parents were reared at high temperature. In addition to these cross‐generational effects, females developed at low temperature had similar flight abilities at low and high ambient temperatures, whereas females developed at high temperature had poorer flight abilities at low than at high ambient temperature. Our findings demonstrate a pronounced benefit of low parental temperature on offspring performance, as well as between‐ and within‐generation effects of acclimation to low temperature. In cooler environments, the offspring generation is expected to develop more rapidly than the parental generation and to comprise more fecund and more dispersive females. By producing phenotypes that are adaptive to the conditions inducing them as well as heritable, cross‐generational plasticity can influence the evolutionary trajectory of populations. The potential for short‐term acclimation to low temperature may allow expanding insect populations to better cope with novel environments and may help to explain the spread and establishment of invasive species.